Role of interleukin-15 and interleukin-18 in the secretion of sIL-6R and sgp130 by human neutrophils - E. Jablonska; M. Marcinczyk (Hindawi Limited, 2003)
Background: Available data indicate that neutrophils (PMN) produce a wide range of cytokines with the potential to modulate immune response. Recent investigation have shown that interleukin (IL)-15 and IL-18 potentiated several functions of normal neutrophils. It has been reported that IL-18-induced cytokine production may be significantly enhanced by coincident addition of IL-15.